Analysis of Gray Water Footprint Changes and Driving Forces Caused by Sectoral Trade in Southeast China - Yu, Fan; Zhang, Chen; Wang, Yuan; Zhu, Lin; Jin, Jianhui; Deng, Haijun; Ling, Hongbo; Shi, Rui; He, Yanmin; Yu, Jinru; Jiang, Peipei (Frontiers in Environmental Science, 2022)
Evaluation of gray water footprint (GWF) flow and its driving mechanism is imperative to trace the source of pollution and formulate the pollution responsibility-sharing strategies to reduce the shortage of water. We quantify the GWF of 22 sectors in Fujian Province in 2002, 2007, 2012, and 2017, using economic input-output life cycle assessment (EIO-LCA) model, and establish a five factors structural decomposition analysis (SDA) model to track the driving forces of the GWF. The results show that the animal husbandry sector of the primary industry is the largest outsourcing sector, being outsourced an average of 7Bm3 GWF by other regions annually. The construction sector is an industry with more pollution outsourcing at the production end, and it should take additional pollution responsibility for its upstream sector. The changes of the GWF in Fujian Province are mainly driven by the final demand per capita and GWF outsourcing. The sector most affected by force drivers is construction, followed by machinery and equipment manufacturing, and other services. This study better reflected the sectoral pollution outsource situation by assessing sectoral GWF flow and net inflow GWF caused by sector trade. We aim at identifying hot sectors of water pollution and sharing the pollution responsibility between upstream and downstream, providing a new perspective to analyze water quality problems in water-rich regions. Besides, our findings imply an urgent need to develop policies related to water pollution transfer for various sectors from a whole supply chain perspective.